Synthesis of Some Biphenyl Compounds by Rearrangement of Salicyl Hydrazones in Polyphosphoric Acid - TIWARI, ALKA (Asian Journal of Chemistry, 2010)
Synthesis of some 3-(3'-carbamoyl-4'-hydroxy phenyl) aldehydes and ketones has been done by the rearrangement of salicyl hydrazones of aromatic aldehydes and ketones using polyphosphoric acid as a reagent. This procedure resulted in higher yields of compounds (75-85%)